Loyalty by obfuscation: Aleksandr Sokurov's Dni zatmeniia vs the Strugatskii brothers' A Billion Years before the End of the World. (June 2015) - Rogatchevski, Andrei
Abstract : This article argues that Aleksandr Sokurov's Days of the Eclipse ( Dni Zatmeniia ; USSR 1988) has been misunderstood as a poor adaptation of the Strugatskii brothers' story, A Billion Years before the End of the World ( Za milliard let do kontsa sveta ; 1976–7). I posit that the film retains enough of the source material to help the viewer make sense of it – especially if the viewer has prior knowledge of this source material. I explore reasons why Sokurov opted for obscuring the Strugatskiis' message as his adaptation strategy, and categorise his approach to film adaptation in the context of his other films and of Strugatskii-related adaptations by other directors.